(untitled) (Scientific journal of the Fergana State University, 2024)
This article provides information on the fabrication and characterization of n-type Bi2Te3 and p-type Sb2Te3 semiconductor thin films. Semiconductor thin films were obtained by thermal evaporation (co-evaporation) on polyimide (kapton) substrate with a thickness of 25 μm. The co-evaporation method is cheap, simple and reliable compared to other methods that take more time to prepare the starting material or require more complex and expensive deposition equipment. Seebeck coefficients of -189 µV·K-1 and +140 µV·K-1 and resistivity of 7.7 7.7 µΩ·m and 15.1 7.7 µΩ·m of n-type and p-type semiconductor thin films were measured at room temperature. These values are better than semiconductor thin films obtained by co-sputtering or electrochemical deposition (ECD) and metal-organic chemical vapor deposition (MOCVD) or flash evaporation. Resulting semiconductor is closer to thin films. Due to their high performance, these semiconductor thin films are used to produce micro-Pelte element useful for temperature control and laser cooling for telecommunications.